(3fQLS GdbdhH GdOGd Edi WQjb GdeMHhHs - (3GdbQTj GdJjej GdHcQj GdMfHdj, CHh GdaQL, GHf GdLhRj, LeGd GdOjf, YHO GdQMef Hf Ydj Hf eMeO, (B597 (3g`s ((3YHO GdbGOQ Hf TGcQ GdQLdIs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdLfI OGQ GdeJbjfhbO GSJNQJ Gddg hCdaJ gPG GdcJGH hGSJNQLJg ef cJH TJi ef cJH GdYdhe hGdCNHGQ Yf GdfHj Udi Gddg Ydjg hSde hbO SejJg fQLS GdbdhH GdOGd Edi WQjb GdeMHhHs
(3BNQgG (B:s
(3hhGQfj Yf QDjI ZjQc hGQaY GdHjf ajeG Hjfj hHjfc jG ef gh GdChd hGdBNQ hGdXGgQ hGdHGWf hgh Hc TSA Ydjes
(3aj BNQg OYGA, hCHjGJ TYQ ddReNTQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3 / 316s
(3eYLe GdeDdajf(B: (3L(B2 / 100s
(3cTa GdXfhf(B: 2 / 1937s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs